FEATURES OF FORMATION OF THE LOGISTICS MANAGEMENT MECHANISM OF THE ENTERPRISE - ROZOVA, ANASTASIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Quality management of logistics activities directly depends on a number of external factors, namely: the level of information infrastructure, the presence or absence of modern logistics information systems, the level of technical and technological support of the production process, the level of automation and mechanization of production processes. fuel, terms of supply, presence or absence of qualified logistics specialists, state of logistics infrastructure, level of development of national and regional institutional infrastructure, level of transport and road infrastructure, presence or absence of automated and mechanized transport equipment, level of national and regional market infrastructure, state of banking system of Ukraine, the number of logistics companies in the logistics market of Ukraine, the level of competitiveness of products and logistics services, the level of material base of the enterprise, etc. The most significant factors of external influence on the quality management of logistics activities of the enterprise are identified, among which are the following: political and legal factors and geo-market or physical factors. During 2019, due to the spread of the acute respiratory disease COVID-19 caused by the SARS-CoV-2 coronavirus, countries began to close their borders and shut down businesses, as well as restrict transportation both internationally and interregionally. This has led to a significant reduction in the level of road haulage in 2020 compared to the previous year. The volume of freight traffic in 2020 to 2019 decreased from 190041.19 thousand tons to 151920.35 thousand tons and accounted for 20%.
Keywords: quality of logistics activity; quality management mechanisms; realization; actual and desired goals of logistics activity; balance of goals of logistics activity